The Integration of Digital Technology in English Language Teaching: A Study on IT-Based Innovation in Vocational High School, Kendari, Southeast Sulawesi - Novi Scorpianti Amrin; Sam Hermansyah; Maulina (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
The rapid advancement of digital technology has revolutionized English language teaching, yet its integration in Indonesian vocational secondary schools remains underexplored. This study examines the implementation of IT-based innovations in English language instruction at one of Vocational Hogh School, Kendari, Southeast Sulawesi, focusing on 29 students in Grade XII TKJ class. Employing a mixed-methods quasi-experimental design, the research integrated quantitative pre- and post-tests with qualitative data from semi-structured interviews, classroom observations, and student questionnaires collected over one semester. Digital tools including Google Classroom, Canva for Education, Quizizz, and video-based authentic materials were systematically incorporated to enhance students’ speaking, listening, reading, and writing skills. Results revealed a statistically significant improvement in overall English proficiency (p < 0.05), with post-test mean scores increasing by 28.4% compared to pre-test scores. Students reported higher motivation (M = 4.21, SD = 0.67 on a 5-point Likert scale) and greater engagement through interactive and collaborative digital activities. Qualitative findings highlighted improved learner autonomy and authentic language exposure, although challenges such as unstable internet connectivity and limited teacher digital competence persisted. This study concludes that strategic integration of IT-based innovations effectively enhances English language learning outcomes in vocational settings. The findings offer practical implications for English teachers and curriculum developers in similar Indonesian vocational high schools and contribute to the growing body of knowledge on technology-enhanced language teaching in developing contexts.